Spatial and temporal trends in alcohol consumption in Belgian cities: A wastewater-based approach. (1st March 2016) - Boogaerts, Tim; Covaci, Adrian; Kinyua, Juliet; Neels, Hugo; van Nuijs, Alexander L.N.
Highlights: Wastewater-based epidemiology to assess alcohol consumption in Belgium. Significant differences in weekly and annual alcohol consumption pattern. Spatial evaluation suggests higher consumption of alcohol when urbanization is higher. Wastewater approach is complementary and additional indicator of alcohol use. Abstract: Background: In recent years, scientific evidence has emerged that wastewater-based epidemiology can deliver complementary information concerning the use of different substances of abuse. In this study, the potential of wastewater-based epidemiology in monitoring spatial and temporal trends in alcohol consumption in different populations in Belgium has been examined. Methods: Concentrations of ethyl sulphate, a minor Phase-II metabolite of ethanol, in 163 influent wastewater samples from eight wastewater treatment plants in Belgium in the period 2013–2015 were measured with liquid chromatography coupled to tandem mass spectrometry and used to estimate alcohol consumption. Results: The highest levels of alcohol consumption were detected in the metropoles Antwerp and Brussels compared to smaller villages. Annual variations were detected, with a higher alcohol consumption measured in 2013 compared with 2014. The weekly pattern showed a clear week and weekend difference in alcohol use, with intermediate levels on Monday and Friday. The results were extrapolated and a use of 5.6 L pure alcohol per year per inhabitant aged 15+ has been estimated in Belgium. The comparison with available information on drinking habits of the Belgian population further demonstrated the usefulness of the wastewater-based epidemiology approach. Conclusions: This is the largest wastewater-based epidemiology study monitoring alcohol consumption to date, demonstrating that objective and quick information on spatio-temporal trends in alcohol consumption on a local and (inter)national scale can be obtained.